EXPLORING THE KNOWLEDGE, ATTITUDE AND BELIEF OF UNIVERSITY STUDENTS REGARDING SUBSTANCE MISUSE - Ali, Salman; Haque, Mohd Asrarul; Ali, Kashif; Javed, Sarah; Shaik, Haneef; Empran, Pranav R. (Journal of Forensic Medicine and Toxicology, 2025)
This study explores university students’ knowledge, attitudes, and beliefs regarding substance misuse, aiming to identify factors that influence drug use behaviors among youth.